Influence of Body Composition on Countermovement Jump Performance in Indian Collegiate Athletes - Kosle, Priyanka Anie; Sanyal, Taniya; Tripathi, Rajatmani (CV Media Inti Teknologi, 2025)
Background of study: In sports, explosive lower-body power is often the difference between good and great performance, especially in movements like jumping. This study explored how body composition, specifically muscle and fat mass, relates to countermovement jump (CMJ) performance in 60 trained Indian collegiate athletes from various sports backgrounds. Methods: Using a bioelectrical impedance analyzer, we measured skeletal muscle mass (SMM) and fat mass (FM), while jump metrics like height, peak force, and peak power were captured using a high-frequency force platform. Result: Our results showed a strong positive link between muscle mass and both peak power (r = 0.792) and force (r = 0.741), and a moderate connection with jump height (r = 0.469). In contrast, fat mass was slightly but negatively related to jump height (r = -0.248) and flight time (r = -0.256), suggesting that excess fat might hold athletes back in movements requiring quick, explosive effort. Conclusion: These findings reinforce what many coaches and athletes observe in practice: more muscle, particularly in the lower body, usually means better jump performance, while unnecessary fat can be a limiting factor. The study highlights the importance of looking beyond total body weight and focusing on the quality of mass an athlete carries.